UTAUT Model in Teaching Biology: Structural Equation Modeling - Muhammad Sofwan (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
This study aims to examine the direct effect of the UTAUT model, educational policies and habits on Information and communication use (ICTuse). These dimensions were developed by proposing research indicators that have a partial and simultaneous impact. With a sample of 251 teachers in teaching Biology. This study uses Structural Equation Modeling (SEM) through partial least square approach (PLS). Based on research findings, this study provides implications for policies/programs that aim to promote teachers to adopt ICT-based teaching. From a managerial and institutional perspective, this research has several implications for policies from stakeholders and the government which aims to prepare aspects of facilities and human resources in facing educational challenges that are closely related to the development of internet technology and integrate them into the learning process in Biology subject.